Magnetic Resonance Enterography and Histology in Patients With Fibrostenotic Crohn's Disease: A Multicenter Study. Issue 7 (13th July 2022) - Coimbra, Alexandre; Rimola, Jordi; Cuatrecasas, Miriam; De Hertogh, Gert; Van Assche, Gert; Vanslembrouck, Ragna; Glerup, Henning; Nielsen, Agnete Hedemann; Hagemann-Madsen, Rikke; Bouhnik, Yoram; Zappa, Magaly; Cazals-Hatem, Dominique; et al.
Abstract : INTRODUCTION: Magnetic resonance enterography (MRE) is useful for detecting bowel strictures, whereas a number of imaging biomarkers may reflect severity of fibrosis burden in Crohn's disease (CD). This study aimed to verify the association of MRE metrics with histologic fibrosis independent of inflammation. METHODS: This prospective European multicenter study performed MRE imaging on 60 patients with CD with bowel strictures before surgical resection. Locations of 61 histological samples were annotated on MRE examinations, followed by central readings using the Chiorean score and measurement of delayed gain of enhancement (DGE), magnetization transfer ratio, T2-weighted MRI sequences (T2R), apparent diffusion coefficient (ADC), and the magnetic resonance index of activity (MaRIA). Correlations of histology and MRE metrics were assessed. Least Absolute Shrinkage and Selection Operator and receiver operator characteristic (ROC) curve analyses were used to select composite MRE scores predictive of histology and to estimate their predictive value. RESULTS: ADC and MaRIA correlated with fibrosis (R = −0.71, P < 0.0001, and 0.59, P < 0.001) and more moderately with inflammation (R = −0.35, P < 0.01, and R = 0.53, P < 0.001). Lower or no correlations of fibrosis or inflammation were found with DGE, magnetization transfer ratio, or T2R. Least Absolute Shrinkage and Selection Operator and ROC identified a composite score of MaRIA, ADC, and DGE as a very good predictor of histologic fibrosis (ROC area under the curve = 0.910). MaRIA alone was the best predictor of histologic inflammation with excellent performance in identifying active histologic inflammation (ROC area under the curve = 0.966). Discussion: MRE-based scores for histologic fibrosis and inflammation may assist in the characterization of CD stenosis and enable development of fibrosis-targeted therapies and clinical treatment of stenotic patients.